The association between the UBQLN1 polymorphism and Alzheimer's disease risk: A systematic review - Li, X.; Zhou, J.; Chen, H.; Wang, F.; Mei, Q.; Sun, H. (Cellular and Molecular Biology, 2017)
Recently, some studies suggested that UBQLN1 variant was associated with AD risk. However, the results were inconsistent. This meta-analysis aimed to determine the association between UBQLN1 variant and AD risk. We searched the electronic databases PubMed, Embase, and CNKI databases. Random-effects model was used. All statistical tests were performed using the STATA 11.0 software (StataCorp, College Station, TX, USA). UBQLN1 variant was not associated with the risk of AD (OR=1.05; 95%CI, 0.92–1.19; I2=35%). The corresponding pooled ORs were not materially altered in sensitivity analysis. The Galbraith plot was used to find the source of the heterogeneity and no study was the outlier. The shape of the funnel plot showed symmetry. Egger's test found no evidence of publication bias (P=0.8). These results suggest that the UBQ-8i polymorphism was not associated with AD risk.